Identity and typification of Linaria ×versicolor (Antirrhineae, Plantaginaceae) - Ruch, Nicolas; Fernández-Mazuecos, Mario; Saez Goñalons, Llorenç (Mediterranean Botany, 2025)
The identity of Linaria ×versicolor (Jacq.) Chaz. is discussed, supporting a hybrid origin in cultivation that involved species of the North African clade of Linaria subsect. Versicolores as parents. Due to the lack of original elements, a specimen from the SEV herbarium is designated as the neotype of the name. Ornamental plants usually known as “Linaria maroccana hort.” correspond to this taxon, and not to L. maroccana Hook.f., one of the putative parents, native to the High Atlas (Morocco).